Uji Model Kualitas Audit: Studi Empiris Perusahaan yang Melakukan IPO di Bursa Efek Indonesia - T. Husain; Melani Quintania; Nedi Hendri (Akuisisi: Jurnal Akuntansi, 2020)
Various financial statement scandals lead to a low public perception of audit quality. The quality of the audit itself can be studied from various perspectives. This research uses the paradigm of thinking to test audit quality modeling in predicting financial ratios consisting of liquidity ratios, activity ratios, solvency ratios, profitability ratios, and market prospect ratios. The type of research is causality with a quantitative approach. The subject of this research uses a public company that does Initial Public Offerings (IPO) in 2019. Data analysis methods use logistic regression analysis. This study's findings show that it meets the model's specifications, with nagelkerke r square score of 0.151, which means it has a weak influence in explaining the model. Besides that, does not yield influence simultaneously with omnibus tests of model coefficients and only one proof of the hypothesis of the Financial Ratio's viz price-to-book value proxy test that has a partially significant effect with the wald testing.